Quercetina e cafeína: efeito no desempenho físico em situação de hipóxia - Schultz, Rossana Velazquez (2017)
Football is one of the most popular sports and during practice there is an increase in the production of reactive species, which can lead to fatigue and even muscle damage. In sports, athletes need an ability to overcome, associated with physiological, biochemical and also psychological factors. All of these factors may exert a positive or negative influence on sports performance according to different situations. The performance of athletes without previous adaptation is negatively influenced by the current conditions at altitudes. The search for new substances to reduce negative effects and increase performance. One of the compounds studied is quercetin, a flavonoid with biological properties capable of improving mental and physical performance and which is widely found in nature. The effects include: anti-inflammatory, antioxidant and psychostimulant activity, as well as, the ability to stimulate mitochondrial biogenesis in humans. Another substance known for its ergogenic effect and commonly used in sports is caffeine by altering alertness, reducing fatigue, improving cognitive performance, reaction time and provoking effects such as changes in the central nervous system, cardiovascular system and homeostasis Of calcium. The objective of this study was to analyze the effect of quercetin and caffeine supplementation on the physical performance of athletes, male, hypoxia situation. The double-blind study consisted of eleven male athletes, who were randomly supplemented with either quercetin (1g / day) or caffeine (4mg.kg-1). After 7 days of supplementation, the first test of maximum physical effort in hypoxia (14% of O2 = 3200m altitude) was performed during which data were collected from Lac, Glic, FC, SSE, Dist and Time,% GC,% Cellular H2O,% Intra and extracellular fluid and biochemical variables (SOD, H2O2, TBARS, NOX, ROS and Thiols). The variables were evaluated during rest, exercise and recovery, except the biochemists that were performed at rest and after exercise. Individuals who ingested quercetin in the first 7 days ingested caffeine, with a 15-day interval between supplements. There was no statistical difference in the% GC,% H2O cell,% intra and extracellular fluids, as well as in the performance variables between the two supplements. When comparing the biochemical variables, it was observed an increase in the production of H2O2, Thiols and NOX for the supplementation with caffeine and for supplementation with quercetin, increase in NOX. In the present study, it was concluded that the effect of quercetin is similar to caffeine compared to performance, but quercetin has a protective action after maximal exercise in hypoxia, which was not observed in caffeine supplementation.